Factores ambientales y su influencia en las infecciones respiratorias agudas, en niños de 0 a 5 años de edad en la ciudadela 10 de Agosto, Babahoyo Los Ríos, octubre 2018 – abril 2019 - Pincay Gavilánez, Julissa (2019)
The objective of this research work is to identify the environmental factors that influence acute respiratory infections in children from 0 to 5 years of age; and in order to develop prevention techniques that manage to avoid complications and thus be able to decrease the morbidity and infant mortality rates. In the present investigative work, the deductive method was used due to the direction that the research takes us; also from this, a quantitative approach was made, to know the antecedents, and the evolution of acute respiratory infections in children from o to 5 years old. Of age to demonstrate the causes that influence this type of diseases. At the time of carrying out the field research, it was possible to identify some environmental factors that influenced respiratory infections, considering that one of the problems that arise is prolonged exposure to environmental factors and the little knowledge that parents have. Of children from 0 to 5 years old about respiratory infections, in addition they do not have the necessary economic resources and lack of care or prevention techniques on the part of health specialists, therefore the government should implement new programs of care and prevention of acute respiratory infections.